Quality of life and visual impairment from cataract in Satkhira district, Bangladesh. Issue 8 (24th July 2008) - Polack, S; Kuper, H; Wadud, Z; Fletcher, A; Foster, A
Abstract : Aims: To evaluate a vision-related quality of life (QOL) scale (World Health Organization Prevention of Blindness and Deafness Visual Function 20—WHO/PBD VF20) and explore the impact of cataract visual impairment on vision- and health-related QOL in people ⩾50 years from Satkhira district, Bangladesh. Method: 217 cases visually impaired from cataract and 280 controls with normal vision were interviewed about vision-related QOL (WHO/PBD VF20), generic health-related QOL (EuroQol generic health instrument, EQ-5D) and socio-demographic information. The validity and reliability of the WHO/PBD VF20 were evaluated using standard psychometric tests and criteria. Results: Evidence for validity and reliability of the WHO/PBD VF20 was found. Worsening general functioning, psychosocial and overall eyesight scores were associated with increased visual loss (p for trend<0.001). Cases were more likely to report problems with each EQ-5D descriptive domain and had poorer self-rated health than controls with normal vision (p<0.001). Conclusion: Demonstration of the validity and reliability of the WHO/PBD VF20 in this population supports its suitability as a tool for assessing vision-related QOL in low-income settings. The poorer health-related QOL in cases compared with controls suggests an impact of cataract visual impairment on perceived health and well-being, beyond vision-specific experience.